Exploring Users' Perceptions and Expectations about Library Service Quality - soroya, saira; Batool, Syeda Hina; Zaheer, Maria; Khalid, Ayesha (Qualitative and Quantitative Methods in Libraries, 2020)
This study investigated the perceptions and expectations of users of the central library of Mirpur University of Science and Technology (MUST), Mirpur Azad Jammu & Kashmir about library service quality. Utilizing case study method, the present study takes the central library of Mirpur University of Science & Technology (MUST), Mirpur Azad Jammu & Kashmir as a case. The sample of the study consisted of BS students and their respective faculty members. The data were collected through questionnaire survey by using the LibQUAL+ instrument, specifically designed to measure the perceptions of the users about the quality of library service. The findings showed that the users were not satisfied with the quality of library services. Their expectation level with library services was very high. Results suggested that male students had high expectation level for library services than of the female students. Similarly, the level of expectation of the students with library services was higher than the faculty members. The participants demanded a better behaviour of staff, improved services, availability of library material in different formats, physical facilities and ambiance of library needed to be improved. This research serves a base line study in improving and expanding the existing services of the library. Furthermore, the selected case library is in developmental phase and students’ perceptions and expectations may provide a guideline to the authorities to take steps in the desired direction.